KONSEP PENDIDIKAN ISLAM MODERN DALAM PERSPEKTIF PEMIKIRAN KH. A. WAHID HASYIM DAN KH. IMAM ZARKASYI - Abdul Wahid Sriyanto (Menara Tebuireng, 2020)
Islamic Education in Indonesia. The period and dynamics of the development of the Muslims. Where there is a Muslim community, then there are many Islamic educational activities that are conducted according to and conditions. The objectives to be conducted in this qualitative research are: 1) To add data information about analysis KH. Abdul Wahid Hasyim in Modern Islamic education; 2) To add data information about the movement KH. Imam Zarkasyi in Modern Islamic education, 3) To know more clearly the concept of Modern Islamic education Perspective KH. Abdul Wahid Hasyim and KH. Imam Zarkasyi. This research uses literature study approach (Library research). Library research is a research by reading and reading the existing literature with the object of research. Library research uses the materials as the subject matter and sub-issues of research. The result of research in the modern educational concept of modern Islam according to KH. Abdul Wahid Hasyim Hasyim's perspective is with the opening of a modern madrasah named Madrasah Nizamiyah with 70% curriculum of general science and 30% of religious knowledge, as well as important foreign language mastery. KH. Wahid Hasyim's contribution to Islamic education is education that is used for school education from high school to college. The concept of modern modern education according to KH.'s perspective. Imam Zarkasyi, an educational curriculum called Kulliyatul Mu 'allimin Al-Islamiyah (KMI), where the 100% increase in religious material and 100% of general material. Foreign language learning and Indonesian language using direct and active methods. KH. Imam Zarkasyi donate Pondok Pesantren Gontor to be managed by institutions of Wakaf Boarding School Darussalam Gontor. Both figures have the same idea to apply modern Islamic education that can not dichotomy in pesantren development besides religious education of general education also require that pesantren can answer challenge of era which keep changing. The only difference is in the application of the curriculum and the use of the language in which each birth is ordered.